(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This research study provides a vivid insight about the contribution of legendary Mr.YogeshwarDutt as a Coach in the game of wrestling. The study was conducted with a help of a self-madequestionnaire which consists of 18 questions measuring the extent to which Mr. YogeshwarDuttcontributed as a coach. The replies to the statements were organized and categorized in such a way thatallowed for all of the questions to be assessed using the Likert scale. Strongly agreed, agreed, disagreedand strongly disagreed were the replies given for each of the items. After doing the analysis, we candetermine that the average score obtained via the completion of a questionnaire provides ameasurement of the degree to which Mr. YogeshwarDutt is accountable for paving the way for Indiansports wrestling as an enthusiastic Coach. The aforementioned questionnaire consists of 18 items,which indicate the degree to which Mr. YogeshwarDutt contributed as a coach. This means that thescores from the descriptive statistics reveal that 48 percent of the respondents selected to agree and49 percent showed strongly agreed. As a result of this, it is not hard to conclude that Mr.YogeshwarDutt was an outstanding coach and the very definition of a sports legend.